Intelligence activities, privacy, and habeas data: a systematization of human rights standards - Uprimny Yepes, Rodrigo (2025)
Based on a review of international legal sources from both the universal human rights system and the European and American human rights systems, in particular, the decision CAJAR vs Colombia of the Interamerican Human Rights Court, the article proposes a systematization of human rights standards that allows for the harmonization of intelligence activities. These are necessary for democracies but pose risks to human rights due to their confidential nature, with the rights to privacy, access to information, and habeas data. In particular, the article presents both normative and institutional standards, notably pointing out that judicial oversight is not sufficient; independent civilian institutions are necessary to monitor and control intelligence activities.